2012
DOI: 10.1167/iovs.12-10400
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1-Deficient Mice Are Highly Sensitive toPseudomonas aeruginosabut Not Herpes Simplex Virus Type 1 Corneal Infection

Abstract: PURPOSE.To determine the role of the chemokine CXCL1 on leukocyte recruitment, cytokine production and host resistance during HSV-1 and Pseudomonas aeruginosa infection.METHODS. Viral titer and bacterial load were compared following infection of wild-type (WT) and CXCL1 À/À mice. Corneal leukocyte recruitment was determined using flow cytometry. Cytokine levels were assessed by luminex-based suspension arrays. Hematoxylin and eosin (H&E) staining, confocal microscopy, and optical coherence tomography (OCT) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Corneal thickness changes using OCT imaging have been reported in an infectious model of P. aeruginosa keratitis in C57BL/6 mice. 32 In this study, we report strain-dependent differences in corneal thickness changes in BALB/c and C57BL/6 mice following TLR9 ligand-induced inflammation. While corneal thickness in C57BL/6 mice peaked at 24 hours post treatment and had returned to baseline levels within 1 week, BALB/c corneas showed a delayed corneal thickness response, with a dramatic (approximately 30%) increase in thickness and evidence of a hyperreflective, subepithelial band at 1 week that may reflect an anterior stromal scarring response.…”
Section: Discussionmentioning
confidence: 77%
“…Corneal thickness changes using OCT imaging have been reported in an infectious model of P. aeruginosa keratitis in C57BL/6 mice. 32 In this study, we report strain-dependent differences in corneal thickness changes in BALB/c and C57BL/6 mice following TLR9 ligand-induced inflammation. While corneal thickness in C57BL/6 mice peaked at 24 hours post treatment and had returned to baseline levels within 1 week, BALB/c corneas showed a delayed corneal thickness response, with a dramatic (approximately 30%) increase in thickness and evidence of a hyperreflective, subepithelial band at 1 week that may reflect an anterior stromal scarring response.…”
Section: Discussionmentioning
confidence: 77%
“…Noninvasive in vivo imaging of the anterior segment was performed on anesthetized animals using a Bioptigen spectral domain optical coherence tomography (SD-OCT) system (Leica Microsystems, Triangle Park, NC) to assess corneal structure and inflammation as previously characterized (28, 29). …”
Section: Methodsmentioning
confidence: 99%
“…Using AS‐OCT, it was reported that Pseudomonas aeruginosa elicited a greater degree of corneal inflammation in patients than other causative organisms of bacterial keratitis . In an experimental model of P. aeruginosa ‐infected microbial keratitis, SD‐OCT demonstrated elevated corneal oedema in Cxcl1 −/− mice, which lack the neutrophil‐attracting chemokine CXCL1, up to 24 hours post‐infection . In this study, SD‐OCT provided a higher sensitivity for detecting clinical corneal pathology compared to histological analysis, with corneal oedema visible at six hours post‐infection using SD‐OCT, but only after 12 hours post‐infection in histology sections .…”
Section: As‐oct Imaging In Animalsmentioning
confidence: 64%
“…Similar to its clinical use, novel applications of AS‐OCT to longitudinally monitor and quantitate the extent of inflammation have been documented in multiple experimental models of ocular inflammation, including uveitis, microbial keratitis, sterile inflammation and dry eye disease . Additionally, AS‐OCT has been used to monitor the resolution of inflammation in experimental models of corneal transplantation and corneal wound healing .…”
Section: As‐oct Imaging In Animalsmentioning
confidence: 99%